Short-Term Electrical Distribution Systems Planning Considering Distributed Generation and Reliability - da Cunha Paiva, Rodrigo Rodrigues; Rueda-Medina, Augusto C. [UNESP]; Mantovani, José Roberto S. [UNESP] (Springer Nature, 2017)
The distribution systems planning consists of finding an optimized configuration, at a low cost, which allows to keep the quality and reliability of energy supply. Distributed generators (DGs) make the planning problem more complex to be solved. Therefore, it is important to develop efficient computational tools to reduce costs and time in decision making, indicating where, when, and what types of components should be installed and/or replaced in the medium voltage electric distribution system in the presence of DGs. This paper proposes a short-term planning methodology for allocation of DGs, capacitor banks, control and protection devices, as well as the possibility of reconductoring of branches for the distribution network, while maintaining the quality of energy supply. The formulated multi-objective problem consists of minimizing the costs associated with investment, technical losses, and non-supplied energy of the distribution system, subject to physical, economic, and operational constraints. The reliability of the system is improved through allocation of control and protection devices and compact aerial structures. This problem is solved through an approach based on the non-dominated sorting genetic algorithm (NSGA-II). Tests were performed in a 135-bus distribution system, and the obtained results show the effectiveness of the proposed methodology.
Keywords: Distributed generation; Distribution systems; Multi-objective optimization; Reliability